What is an education paper?. (12th July 2021) - KRISHNAMURTHI, SHRIRAM
Abstract : We recently renamed our "education" track's papers from Education Pearl to Education Matters. This would be a good time to explain our vision for the track as a whole, as well as this specific renaming.